Genomic characterization of Plasmodium falciparum genes associated with anti-folate drug resistance and treatment outcomes in eastern India: A molecular surveillance study from 2008 to 2017 - Das, Sabyasachi; Tripathy, Satyajit; Das, Ankita; Sharma, Meenakshi Kumari; Nag, Ayan; Hati, Amiya Kumar; Roy, Somenath (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract: After being used vigorously for the previous two decades to treat P. falciparum, chloroquine and sulfadoxine-pyrimethamine were replaced in 2009 with an artemisinin-based combination therapy (artesunate-sulfadoxine-pyrimethamine) in an effort to combat multidrug-resistant parasites. We set out to assess the genetic variants of sulfadoxine-pyrimethamine resistance and the effectiveness of its treatment in eastern India prior to, during, and six to eight years following the introduction of the new pharmacological regime. In 2008-2009, 318 P. falciparum-positive patients got the recommended doses of sulfadoxine-pyrimethamine. We used 379 additional isolates from 2015 to 2017 in addition to the 106 isolates from 2010. All 803 isolates from two study sites underwent in-vitro sulfadoxine-pyrimethamine sensitivity testing and genomic characterisation of sulfadoxine-pyrimethamine resistance (pfdhfr and pfdhps). In Kolkata and Purulia, we observed early treatment failure in 30.7% and 14.4% of patients, respectively, whereas recrudescence was found in 8.1% and 13.4% of patients, respectively, in 2008-2009. In 2017, the proportion of in-vitro pyrimethamine and sulfadoxine resistance steadily grew in Kolkata and Purulia despite single use of sulfadoxine-pyrimethamine. Treatment failures with sulfadoxine-pyrimethamine were linked to quintuple or quadruple-pfdhfr-pfdhps mutations (AICII-AGKAT, AICII-AGKAA, AICII-SGKGT, AICII-AGKAA, AICNI-AGKAA) in 2008–2009 (p<0.001). The subsequent spread of mutant-haplotypes with higher in-vitro sulfadoxine-pyrimethamine resistance (p<0.001), such as the sextuple (dhfr-AIRNI+dhps-AGEAA, dhfr- ANRNL + dhps-AGEAA) and septuple (dhfr -AIRNI + dhps-AGEAT), confirmed the progressive increase in antifolate resistance even after an 8-year withdrawal of sulfadoxine-pyrimethamine.